Spin distribution of the nuclear level density in a shell model approach - Newman, Luke; Karampagia, Sofia (HNPS Advances in Nuclear Physics, 2022)
Nuclear level densities (NLDs) are key ingredients in calculations of neutron capture rates for neutron rich isotopes in nuclear astrophysics applications. Available experimental NLDs are limited mainly to nuclei near stability. Therefore, theoretical models are employed to predict the NLDs of neutron rich nuclei. Here we present a methodology for calculating spin- and parity- dependent NLDs using methods of statistical spectroscopy, based on the Shell Model. The spin distribution of the NLDs is predicted for nuclei in the sd and pf shells.